Cheap Talk, Gullibility, and Welfare in an Environmental Taxation Game - Christophe Deissenberg; Herbert Dawid; Pavel Sevcik (Fondazione Eni Enrico Mattei (FEEM), 2004)
We consider a simple dynamic model of environmental taxation that exhibits time inconsistency. There are two categories of firms, Believers, who take the tax announcements made by the Regulator to face value, and Non-Believers, who perfectly anticipate the Regulator's decisions, albeit at a cost. The proportion of Believers and Non- Believers changes over time depending on the relative profits of both groups. We show that the Regulator can use misleading tax announcements to steer the economy to an equilibrium that is Pareto superior to the solutions usually suggested in the literature. Depending upon the initial proportion of Believers, the Regulator may prefer a fast or a low speed of reaction of the firms to differences in Believers/Non-Believers profits.
Keywords: H23; H3; Q5; C69; C79; D62; 330; Environmental policy; Emissions taxes; Time inconsistency; Heterogeneous agents; Bounded rationality; Learning; Multiple equilibria; Stackelberg games; Ökosteuer; Umweltpolitik; Zeitkonsistenz; Begrenzte Rationalität; Lernprozess; Spieltheorie; Theorie